Integrating the ‘Other’ in Adult Education Curriculum: The Case of an Indian Tradition - Linda Ziegahn; Beloo Mehra (Adult Education Research Conference, 2006)
In order to truly globalize the field of adult education, a de-centering of Euro-centric frameworks is needed as we simultaneously integrate non-Western knowledge systems in curricular offerings and theoretical development. This paper explores selected aspects of the philosophy and discipline of Integral Yoga, and presents an example of a curriculum innovation.
Keywords: Transformational learning; spirituality; Indian traditions; Yogic Studies